1996
DOI: 10.1080/09670269600651511
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of intertidal and subtidal red algae to UVA and UVB radiation, as monitored by Chlorophyll fluorescence measurements: Influence of collection depth and season, and length of irradiation

Abstract: Thirteen species from the red algal flora of Helgoland (southern North Sea) were exposed to UVA ÷ UVB radiation for various periods in the laboratory, and dark-adapted variable fluorescence (F v : Fro) was measured immediately after the UV treatment and again after various recovery times in white light. With the exception of Porphyra ~mbilicalis, all species showed a decrease in F v : F m on exposure to UV radiation, followed by recovery towards the initial values during the next 24-48 h in white light. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 22 publications
6
92
1
7
Order By: Relevance
“…Thus, deeper-growing species display a greater decrease of F v /F m in response to UVR exposure than do shallower-growing species. This type of relationship between photoinhibition and depth distribution has been reported previously for several species of marine macroalgae (Dring et al 1996;Hanelt et al 1997;Hanelt 1998;Bischof et al 2000b) and zooxanthellate corals (Shick et al 1995).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, deeper-growing species display a greater decrease of F v /F m in response to UVR exposure than do shallower-growing species. This type of relationship between photoinhibition and depth distribution has been reported previously for several species of marine macroalgae (Dring et al 1996;Hanelt et al 1997;Hanelt 1998;Bischof et al 2000b) and zooxanthellate corals (Shick et al 1995).…”
Section: Discussionmentioning
confidence: 76%
“…It has also been shown that organisms can have markedly different tolerances of UVR (e.g. Bothwell et al 1993;Dring et al 1996;Vinebrooke and Leavitt 1999). These observations have given rise to considerations of what role UVR may currently play in structuring aquatic communities.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, there is agreement that the species sensitivity to solar radiation stress is a function of depth distribution (Dring et al 1996b;Larkum and Wood 1993;Hanelt et al 1997a, c;Hanelt 1998;Bischof et al 1998a;Yakovleva et al 1998). Moreover, some authors regard solar UVB as one of the most important factors controlling the upper distribution limit of seaweeds in the field (Maegawa et al 1993).…”
Section: Depth Zonationmentioning
confidence: 90%
“…For the vertical distribution of tropical seagrasses UV radiation was also proven to be an important factor (Dawson and Dennison 1996). Dring et al (1996b) showed that sensitivity to UV in red algae growing around the island of Helgoland (Germany) varies with species and depth of collection. As for UVB radiation, investigations on the photoinhibition induced by high levels of PAR also shows a correlation between depth-zonation and the ability for dynamic photoinhibition of macroalgae both from sublittoral (Hanelt 1992(Hanelt , 1998Hanelt et al 1994Hanelt et al , 1997a and intertidal populations In support of this concept the green algae Enteromorpha bulbosa and Acrosiphonia arcta which occur in the middle and lower eulittoral at the Antarctic Peninsula (Wiencke and Clayton 2002) do almost show no negative UV-effects on photosynthesis and are able to acclimate to even further elevated UV-exposure within hours or days .…”
Section: Depth Zonationmentioning
confidence: 99%
“…Porphyra is frequently exposed to elevated intensities of UV radiation in the intertidal zone and shows remarkable tolerance to both UV-A and UV-B (50,51). Porphyra has at least two strategies to protect photosynthesis and other key cellular processes from UV damage: mycosporine-like amino acids (MAAs) and circadian control over the timing of UVsensitive processes.…”
Section: Significancementioning
confidence: 99%